Evaluation of PCA in herbs identification - Mohamad Radzi, Nur Fadzilah; Che Soh, Azura; Mohamad Yusof, Umi Kalsom; Ishak, Asnor Juraiza; Hassan, Mohd Khair; Ahmad, Siti Anom; Khamis, Shamsul (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
Many of the existing herbs species on the earth are still unknown. Each herb species has unique odor which differs from each other. This odor parameter is used to differentiate the type of herbs species by using gas sensor array. The response of electrical signal is generated when the gas sensor array detect the odor of herb species. This paper presents a pattern analysis of electrical signal data by using principle component analysis method. 4 different herb species with same group family (Family Lauraceae) were investigated. The result shows the discrimination between herb species is possible.